Factors Affecting Successful Capital Raising for Startups: Evidence from the US Capital Market - Kraszek, Rafał; Spirzewski, Krzysztof (Czynniki wpływające na skuteczne pozyskiwanie kapitału przez startupy: przykład z amerykańskiego rynku kapitałowego, 2025)
Aim: This article aimed to analyse the selected factors that have an impact on the success of acquiring capital of a startup company on the capital market. The discussed research question was: Does information, such as the founder’s background, education, experience, and amount of funding acquired previously, have a positive impact on the amount of capital that will be acquired in the next rounds of funding? Methodology: An econometric analysis was performed on the effect of the entrepreneur’s experience and background on the success of the next rounds of funding, using an OLS linear regression model. The study used selected factors that analysed data on the US market. Results: The model’s joint statistical significance suggests that the explanatory variables have an effect on the explained variable. Implications and recommendations: The results may be important for new startup companies requiring external financing from capital markets. The study focused on the initial financing situation of startups based on data from the USA. Originality/value: The main value of the research was the identification of factors showing low significance (type of profession: consultant, teacher, Google or Microsoft employee) and those significant (e.g. profession of director).
Financial Sciences. Nauki o Finansach, 2025, vol. 30, no. 1, s. 1-13
Keywords: startup; capital markets; venture capital; startupy; rynek kapitałowy